Perception and awareness of circular economy options within sectors related to agriculture in Argentina [Submitted Version] - Rotolo, Gloria Claudia; Vasillo, Chiara; Rodriguez Aranza, Ailén; Magnano, Luciana; Milo Vaccaro, Marcelo; Civit, Bárbara María; Covacevich, Melina Soledad; Arena, Alejandro Pablo; Ulgiati, Sergio (2022)
European Commission via the Horizon 2020-MSCA-RISE-2018 Program, under Project Nº 823967 named “Promoting circular economy in the supply chain” (ProCEedS). -- European Commission’s research program Horizon 2020-SC5-2020-2 scheme, Grant Agreement 101003491 (JUST Transition to the Circular Economy project).